Perilaku Merokok Pada Remaja Perumpuan(Studi Kualitatif Mengenai Perilaku Merokok Pada Remaja Perempuan) - PUTRA, RESKA WIDIA (2007)
Modernization as we known, has giving many consequences. A period was called 'Agony Period' impact to human living. Technology and modernization become a new social economic factors in healthy aspect. Adolescence as a social member, showed risk behavior like smoking. Smoking become familiar and massive using, in fact that is many consequences accepted to smokers. Not only male adolescence who showed smoking behavior but also female adolescence. Further, for female smokers, many medical effects become consequences within, like: infection reproduction organ, impotent, heart desease, breast cancer, dysmenorrahoe, Sudden Infant Death Syndrome (SIDS) and many others. Indeed, Indonesians female smokers faced a negative perspective from public. Eastern culture that become principle our society explained, smoking for female it is not just a good behavior. This qualitative study try to explain smoking behavior at female adolescence. Interview, observation, documentation and inventory personality test were been used to give comprehensive explanations. Characteristics of subject studies are: female, age average between 17 to 21 years old, smoking for at least one year, living at city of Surakarta. Analize procedure in this study, shown psychological dynamization in smoking behavior at female adolescence smoker. Besides having a group who are smoker, curiousity become a reason for female adolescence to smoke for the first time. In addition, style of parenting which is permissive, influenced smoking behavior become exist to female adolescence. In fact parents give modelling undirectly to female adolescence to smoke. Female adolescence face many problem in their life which is impact emotional aspect and make them to smoke continuously. Female adolescence also knowing about negative perspective from society, that giving impact for smoking more carefully. Neither, female adolescence known about moral values (religion) not accepted smoking behavior, but smoking still become a choice for feeling more comfortable, calm and relax, this is also become a reason why they found difficulties to quit from smoke. Even they have managed to quit smoking, the long term xiv sucsess is poor. Doing sport exercise and drinking water, become coping strategies to reduce the medical effect of their smoking behavior. Smoking is not only embedded in the immediate material circumstances in which smoker lives, but also in the wider social and cultural context within which smoking is prevently. Family as a first social system have responsibility to take care their child. Supporting parenting style would impact to developmental psychological aspect of their child. Public also have responsibility to give modelling of healthy living. Government, supported to make a policy and also preventive and promotive programs designed. Parents, school, public and government involved, together to prevent and care smoking behavior at female adolescence smokers. Save our generations..